Precarious Work. - Kalleberg, Arne L. (Research in the sociology of work., 2017)
This volume presents original theory and research on precarious work in various parts of the world, identifying its social, political and economic origins, its manifestations in the USA, Europe, Asia, and the Global South, and its consequences for personal and family life.